Strategic Development of the Coffee Commodity Business at the Mandalagiri Coffee Producers Cooperative - Ahmad Mufid; Ujang Sumarwan; Mimin Aminah (Postgraduate, University of Mataram, 2025)
Coffee is one of Indonesia’s strategic plantation commodities with high economic value and a significant role in supporting the national economy. This study aims to formulate a business development strategy for the coffee commodity at the Mandalagiri Coffee Producers Cooperative, located in Garut Regency, West Java. The research employs a descriptive qualitative method and strategic analysis, with data analyzed using the Business Model Canvas (BMC), SWOT, Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), Quantitative Strategic Planning Matrix (QSPM), and Simple Additive Weighting (SAW). The SWOT analysis based on the BMC indicates that Mandalagiri Cooperative possesses strengths in product quality and customer loyalty but remains weak in diversification and digitalization, presenting significant opportunities in niche markets while facing challenges from digital competitors. The IFE score (2.80) and EFE score (3.13) suggest the cooperative is in a strategic position to grow through product development and market expansion. Priority strategies include B2B/B2C expansion, brand strengthening, derivative product development, and the formation of a digital marketing team. These strategies were validated using the SAW method and formulated into a new business model emphasizing digital distribution, customer education, and brand image enhancement. Therefore, business development strategies can be implemented through strengthening distribution channels, improving customer relationships, and undergoing digital transformation toward a more adaptive and sustainable business model.